Mild functional decline and driving performance of older drivers without a diagnosed dementia: Study of leukoaraiosis and cognitive function. (November 2020) - Renge, Kazumi; Park, Kaechang; Tada, Masahiro; Kimura, Toshiaki; Imai, Yasuo
Highlights: We investigated the influences of cognitive decline on the driving performance of older drivers. Test drives on a close-circuit course were conducted at a driving school. Leukoaraiosis and cognitive function were assessed using MRI and MMSE, respectively. Driving behaviors were assessed using instructor evaluations and instruments. LA grade and MMSE scores could predict some aspects of poor driving performance in older drivers. Abstract: Motor vehicle collisions involving older drivers have increased and become an important social issue. It is known that the decline of cognitive function, including dementia, affects driving performance. A series of studies using the Mini-Mental State Examination (MMSE) and other tests of dementia have attempted to prevent motor vehicle collisions by identifying as early as possible older drivers who may be unable to maintain their driving performance. Further, the performance of older drivers may deteriorate even if they do not have a diagnosis of dementia. Therefore we focused on the relationship between cognitive functioning assessed by the MMSE and diagnosis of leukoaraiosis (LA), or changes in the cerebral white matter, with different aspects of driving behavior resulting from aging. Qualified driving instructors evaluated participants' driving behaviors on an outdoor driving course at a driving school. Visual search duration and angle at intersections were obtained by wearable wireless sensors. Vehicle speed and minimum vehicle speed were recorded from vehicle speed pulse signals. Duration of signaling and visual searches at unsignalized intersections were recorded using an in-vehicle camera. We assessed instructors' evaluations and the scores on two instruments to evaluate the effects of MMSE scores and the grade of LA on driving performance were verified. The results suggest that lower MMSE scores and higher LA grade can predict some aspects of poor driving performance in older drivers before they experience dementia or an evident decline in cognitive functioning. Based on these results, we discuss countermeasures that may prevent motor vehicle collisions involving older drivers.